Confronting decline : the political economy of deindustrialization in twentieth-century New England - Koistinen, David. (Working in the Americas, 2014)
Focuses on Massachusetts textile industries to understand the process of deindustrialization and three common responses to it: cutbacks in regulation, federal intervention, and economic development.